Free Tissue Transfer with Distraction Osteogenesis and Masquelet Technique Is Effective for Limb Salvage in Patients with Gustilo Type IIIB Open Fractures. Issue 4 (April 2020) - Abdou, Salma A.; Stranix, John T.; Daar, David A.; Mehta, Devan D.; McLaurin, Toni; Tejwani, Nirmal; Saadeh, Pierre B.; Levine, Jamie P.; Leucht, Philipp; Thanik, Vishal D.
Abstract : Summary: Osteocutaneous reconstruction can be challenging because of concomitant injuries and limited donor sites. There is a paucity of data on limb salvage outcomes following combined soft-tissue reconstruction and bone transport or Masquelet procedures. The authors reviewed a consecutive series of open tibia fracture patients undergoing soft-tissue reconstruction with either distraction osteogenesis or Masquelet technique. Endpoints were perioperative flap complications and bone union. Fourteen patients with Gustilo type IIIB open tibia fractures were included. Half of the group received muscle flaps and the remaining half received fasciocutaneous flaps. Ten patients (71.4 percent) underwent distraction osteogenesis and the remaining patients underwent Masquelet technique. Average bone gap length was 65.7 ± 31.3 mm (range, 20 to 120 mm). In the bone transport group, the average external fixation duration was 245 days (range, 47 to 686 days). In the Masquelet group, the average duration of the first stage of this two-stage procedure (i.e., time from cement spacer placement to bone grafting) was 95 days (range, 42 to 181 days). Bone union rate, as determined by radiographic evidence, was 85.7 percent. There was one complete flap failure (7.1 percent). One patient underwent below-knee amputation after failing bone transport and developing chronic osteomyelitis and subsequent infected nonunion. Our case series demonstrates that nonosteocutaneous flap methods of limb reconstruction are a viable option in patients with segmental long bone defects, with a bone union rate of 85 percent and a limb salvage rate over 90 percent in patients with Gustilo type IIIB fractures. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.